2010
DOI: 10.1177/0013124510380717
|View full text |Cite
|
Sign up to set email alerts
|

Metal Detectors and Feeling Safe at School

Abstract: This article argues that metal detectors bestow an organizational stigma to schools. One symptom of this is students' heightened level of fear at school. Using data from the National Longitudinal Study of Adolescent Health (Add Health) and a matched-pair design, this study finds that metal detectors are negatively correlated with students' sense of safety at school, net of the level of violence at school. However, this association is different for urban students. The negative association between metal detector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 18 publications
2
32
0
Order By: Relevance
“…Moreover, this finding supports results from previous studies suggesting that students in schools with metal detectors tend to feel less safe than students at schools without such security measures (e.g., Gastic, 2011;Hankin, Hertz, & Simon, 2011).…”
Section: Impact Of School Security Measuressupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, this finding supports results from previous studies suggesting that students in schools with metal detectors tend to feel less safe than students at schools without such security measures (e.g., Gastic, 2011;Hankin, Hertz, & Simon, 2011).…”
Section: Impact Of School Security Measuressupporting
confidence: 89%
“…Overall, study findings indicate that the presence of metal detectors was associated with increased concerns for safety among students, and these concerns were compounded by the number of visible security measures present in the school environment. Moreover, this finding supports results from previous studies suggesting that students in schools with metal detectors tend to feel less safe than students at schools without such security measures (e.g., Gastic, ; Hankin, Hertz, & Simon, ).…”
Section: Students’ Perceptions Of Safety At Schoolsupporting
confidence: 88%
See 1 more Smart Citation
“…In this regard, metal detectors have been associated with both elevated (Bachman, Randolph, & Brown, 2011;Gastic, 2011; and reduced (Tillyer, Fisher, & Wilcox, 2011) fear at school. Studies of the relationship between metal detectors and students' attitudes about school policies are similarly mixed.…”
mentioning
confidence: 99%
“…Multi-tiered systems of support security cameras, or guards in schools prevents school violence (Tanner-Smith, Fisher, Addington, & Gardella, 2018), and some research has found that such measures are associated with more incidents of crime and violence at school (Nickerson & Martens, 2008;Steinka-Fry, Fisher, & Tanner-Smith, 2016). Even more importantly, many students feel such measures are unnecessary (Bracy, 2011) and feel less safe when they are in place (Bachman, Randolph, & Brown, 2011;Gastic, 2011;Perumean-Chaney & Sutton, 2013). A quick fix is not the answer; instead school safety requires a more comprehensive approach to both preventing fatal violence while promoting supportive school environments and mental and behavioral health of all students.…”
Section: Tablementioning
confidence: 99%